Safety of early discharge in low risk patients after acute ST-segment elevation myocardial infarction, treated with primary percutaneous coronary intervention. Open label, randomized trial - Novobilsky, Kamil; Stipal, Roman; Cerny, Petr; Horak, Ivo; Kaucak, Vladimir; Mrozek, Jan; Vaclavik, Jan; Kryza, Radim (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
BACKGROUND: The length of hospital stay in patients with acute myocardial infarction and ST-segment elevation (STEMI) has been shortened in recent years with corresponding savings in costs, but there is limited available data on its implementation in clinical practice. The aim of this trial was to determine whether early discharge in selected patients after STEMI is feasible and safe. METHODS: 151 patients with STEMI successfully treated with primary percutaneous coronary intervention (PCI) who fulfilled the inclusion criteria of low risk were randomly assigned to two groups on a 1:1 ratio: early (within 48-72 h of admission) and standard (after 72 h) discharge. The primary end point was the composite of death, myocardial infarction (MI), unstable angina, stroke, unplanned rehospitalization, repeated target vessel revascularization and stent thrombosis at 90 days after discharge. The study is registered with ClinicalTrials.gov (identifier NCT02023983). RESULTS: The primary end point occurred in 5 patients in the early group and 6 in the standard group (6.6% vs. 8.0%, P=0.765). There were no significant differences in the incidence of individual components of the primary end point at 90 days. The length of hospital stay was significantly shorter in the intervention group (60.8 ± 8.5 vs. 92.1 ± 12.1 h, P<0.0001). CONCLUSION: This study confirms that early discharge within 48-72 h in selected low risk patients after STEMI treated with successful primary PCI is feasible and safe, with outcomes comparable to the later discharge. This strategy applies to more than a quarter of all STEMI patients.
Keywords: senioři; propuštění pacienta; infarkt myokardu s elevacemi ST úseků; ST Elevation Myocardial Infarction; percutaneous coronary intervention; ST elevation myocardial infarction; Time Factors; Length of Stay; délka pobytu; safety; výsledek terapie; mužské pohlaví; Prospective Studies; Monitoring, Physiologic; kontinuita péče o pacienty; ženské pohlaví; Humans; prospektivní studie; časové faktory; koronární angioplastika; Percutaneous Coronary Intervention; Patient Discharge; patient discharge; monitorování fyziologických funkcí; feasibility; Continuity of Patient Care; Female; Aged; Treatment Outcome; lidé; Male